Analisis Yuridis Penentuan Jenis Dakwaan Yang Disangkakan Kepada Terdakwa Dalam Perkara Tindak Pidana Narkotika - Boyman Berkat Humendru; Devi Anggara br Ginting; Rico Natanael Sitorus (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This article is aimed to find out the legal basis of the public prosecutor in determining the type of indictment of a narcotics offender. The basis for making the indictment is regulated in KUHP article 143 paragraph (2) and the circular of the attorney general no. 009/19/11/1993. Seeing the narcotics abuse in Indonesia is always increasing in all circles nowadays. S there needs to be a real punishment for uses and dealers. In the prosecution process, a defendant in a narvotics crime will be charged with an alternative indictment. Alternative indictments are composed of several criminal offences which exclude one another from the other.